The Experimental Plant and Modeling Method for Spatial Waves in Multicoupled Quasi-Optical Systems with Periodic Inhomogeneities - G.S. Vorobjov; V.O. Zhurba; A.S. Krivets; M.V. Petrovskii; A.A. Rybalko; A.I. Ruban; Yu.V. Shulga (Журнал нано- та електронної фізики)
The experimental plant and the general method of modeling of electromagnetic wave processes in multicoupled quasi-optical systems are described. Examples of choosing the optimum regimes of modeling and basic parameters of the investigated electrodynamic systems are shown. The functional scheme of the experimental plant is also described. The general method of modeling of electromagnetic phenomena in resonant and waveguide multicoupled quasi-optical systems is presented for the first time.